Melampaui Ruang Kelas: Pemberdayaan Mahasiswa Perbatasan melalui Workshop Kepemimpinan dan Inovasi Bisnis - Shalahuddin Shalahuddin; Mohamad Nur Utomo; Kaujan Kaujan; Tinik Sugiati; Budi Hasyim; Rahmi Nur Islami; Nurjannatul Hasanah; Meylin Rahmawati; Ferawati Usman; Aswan Aswan; Sigit Firmansyah; Gusti Ayu Dwi Jessika (Universitas Ichsan Sidenreng Rappang, 2025)
This community service activity aimed to enhance the leadership capacity and business innovation of students at the Faculty of Economics, Universitas Borneo Tarakan, as future economic actors in the Indonesia–Malaysia border area. The activity was implemented through a participatory and collaborative approach consisting of five main stages: socialization and problem mapping, training and workshop, technology application and practical simulation, mentoring and evaluation, and sustainability program development. The results showed achievements exceeding the targets, with 85% of participants completing the entire training series, 12 business proposals using the Business Model Canvas (BMC) framework, and 18 participants successfully creating active digital business accounts. The improvement in participants' abilities was reflected in the pre-test and post-test results, which showed an average score increase of 28% in leadership aspects and 34% in business innovation aspects. The campus market simulation through the Student Business Expo successfully strengthened collaborative networks among students, local MSMEs, and the local entrepreneurial community. This activity significantly contributed to shaping students' entrepreneurial character and competencies while supporting the strengthening of the creative economy ecosystem in the border region.